Immortalised murine R349P desmin knock-in myotubes exhibit a reduced proton leak and decreased ADP/ATP translocase levels in purified mitochondria - Berwanger, Carolin; Terres, Dominic; Pesta, Dominik; Eggers, Britta; Marcus, Katrin; Wittig, Ilka; Wiesner, Rudolf J.; Schröder, Rolf; Clemen, Christoph S. (European Journal of Cell Biology, 2024)
Desmin gene mutations cause myopathies and cardiomyopathies. Our previously characterised R349P desminopathy mice, which carry the ortholog of the common human desmin mutation R350P, showed marked alterations in mitochondrial morphology and function in muscle tissue. By isolating skeletal muscle myoblasts from offspring of R349P desminopathy and p53 knock-out mice, we established an immortalised cellular disease model. Heterozygous and homozygous R349P desmin knock-in and wild-type myoblasts could be well differentiated into multinucleated spontaneously contracting myotubes. The desminopathy myoblasts showed the characteristic disruption of the desmin cytoskeleton and desmin protein aggregation, and the desminopathy myotubes showed the characteristic myofibrillar irregularities. Long-term electrical pulse stimulation promoted myotube differentiation and markedly increased their spontaneous contraction rate. In both heterozygous and homozygous R349P desminopathy myotubes, this treatment restored a regular myofibrillar cross-striation pattern as seen in wild-type myotubes. High-resolution respirometry of mitochondria purified from myotubes by density gradient ultracentrifugation revealed normal oxidative phosphorylation capacity, but a significantly reduced proton leak in mitochondria from the homozygous R349P desmin knock-in cells. Consistent with a reduced proton flux across the inner mitochondrial membrane, our quantitative proteomic analysis of the purified mitochondria revealed significantly reduced levels of ADP/ATP translocases in the homozygous R349P desmin knock-in genotype. As this alteration was also detected in the soleus muscle of R349P desminopathy mice, which, in contrast to the mitochondria purified from cultured cells, showed a variety of other dysregulated mitochondrial proteins, we consider this finding to be an early step in the pathogenesis of secondary mitochondriopathy in desminopathy.
CRIS-Team Scopus Importer:2024-03-15
Keywords: ADP/ATP translocase; Desminopathy; Electrical pulse stimulation; Immortalised murine myoblasts; Mitochondrial respiration; Myofibrillar maturation